Bone and joint changes in patients with porphyria turcica: a clinical and roentgenologic study - Doğramacı, İhsan; Kenanoğlu, Abdullah; Müftü, Yunus; Ergene, Turhan; Wray, Joe D. (The Turkish Journal of Pediatrics, 1962)
In over half of three hundred and seventy-six patients with porphyria turcica, secondary to consumption of hexachlorobenzene treated wheat, joint involvement was observed.The striking feature was swelling and spindling of the fingers, usually in a symmetrical fashion. Roentgenologic examination of eighteen patients showed osteoporosis which was notably restricted to the phalanges, the metacarpal and carpal bones, and the distal metaphysis and epiphysis of both the ulna and the radius and to the corresponding bones of the lower extremities.Interphalangeal arthritis leading to the narrowing of the joint spaces was striking and resembled in a way the changes of rheumatoid arthritis.In two cases erosion of the terminal phalanges was seen.Despite the lapse of one to two years after the termination of other porphyria symptoms, including cessation of abnormal excretion of porphyrins, the joint lesions were found to be still present